2021
DOI: 10.2174/1874210602115010071
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Root Filled Teeth; Current Opinions and Techniques

Abstract: Purpose: To examine current decision-making preferences of Jordanian dentists when Restoring Root Filled Teeth (RFT). Materials and Methods: 834 Jordanian general dentists, prosthodontists and endodontists were invited to participate in a validated online survey with a 62% participation rate. Respondents were invited to answer 24 questions about their preferences for techniques and materials they use to restore RFT. The questions aimed at exploring restorative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
(14 reference statements)
2
3
0
Order By: Relevance
“…The present analysis is consistent with a prior study conducted in Saudi Arabia, which found that the favored material for endocrown was lithium disilicate [18,22]. The study conducted by Wahab et al investigated the material preferences for endocrown among dentists in Jordan, and their findings aligned with the previously described research [16].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The present analysis is consistent with a prior study conducted in Saudi Arabia, which found that the favored material for endocrown was lithium disilicate [18,22]. The study conducted by Wahab et al investigated the material preferences for endocrown among dentists in Jordan, and their findings aligned with the previously described research [16].…”
Section: Discussionsupporting
confidence: 91%
“…The primary aim of employing the endocrown approach is to preserve the pre-existing tooth structure that can be utilized for bonding purposes, while simultaneously guaranteeing the biomechanical stability of teeth that have undergone endodontic treatment and may possess reduced structural integrity. The endocrown has been demonstrated to have enhanced mechanical qualities, leading to minimal tooth structure loss, reduced clinical interventions, decreased costs, and enhanced cosmetic results [15][16][17][18][19][20]. Therefore, the objective of this cross-sectional study was to assess the level of knowledge and opinions of dental practitioners on the utilization of endocrown as a s a postendodontic treatment technique.…”
Section: Discussionmentioning
confidence: 99%
“…However, while using this approach, the preparatory design and material selection should be considered [ 23 , 29 , 30 ]. Similar findings were recording by Wahab et al, who investigated the preferences of Jordanian dentists for EC materials [ 22 ]. The present study demonstrated the related finding that most participants (63.46%) preferred LDGC as the material of choice for EC.…”
Section: Discussionsupporting
confidence: 88%
“…Following the findings of multiple survey studies on dentists, this study found that prefabricated post/core is the most preferred technique among the participants ( Sarkis-Onofre et al, 2015 , Wahab et al, 2021 ), followed by endocrown, and cast post and core.…”
Section: Discussionmentioning
confidence: 83%